2020
DOI: 10.1111/1442-1984.12299
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of diurnal and nocturnal pollinators for reproduction in the early spring flowering shrub Stachyurus praecox (Stachyuraceae)

Abstract: Generalized pollination systems may be favored in early spring flowering plants, as during this period pollinator activity is unpredictable. Many previous studies have concentrated on the importance of diurnal visitors in pollination, and consequently, information on the contribution of nocturnal visitors to pollination in early spring is limited. This study was conducted to evaluate the relative importance of diurnal and nocturnal pollinators in the early spring flowering dioecious shrub Stachyurus praecox (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Phenology is an integrative environmental science studying the timing of recurrent biological events related to climate and its effects on different species of plants and animals (Morellato et al, 2016). Studies examining the phenology of dioecious species, with different pollination modes and from diverse phylogenetic lineages, are relevant for understanding the influence of sexual selection on the evolution and maintenance of sexual dimorphism and sex allocation in plants (Escobedo‐Sarti & Mondragón, 2016; Morellato, 2004; Munguia‐Rosas et al, 2011) because overlapping between sexes is essential for reproductive success (Funamoto & Sugiura, 2021; Lazcano‐Lara & Ackerman, 2018; Morellato, 2004; Obeso, 2002; Octavio‐Aguilar, Iglesias‐Andreu, et al, 2017; Segalla, Pinheiro, & Morellato, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Phenology is an integrative environmental science studying the timing of recurrent biological events related to climate and its effects on different species of plants and animals (Morellato et al, 2016). Studies examining the phenology of dioecious species, with different pollination modes and from diverse phylogenetic lineages, are relevant for understanding the influence of sexual selection on the evolution and maintenance of sexual dimorphism and sex allocation in plants (Escobedo‐Sarti & Mondragón, 2016; Morellato, 2004; Munguia‐Rosas et al, 2011) because overlapping between sexes is essential for reproductive success (Funamoto & Sugiura, 2021; Lazcano‐Lara & Ackerman, 2018; Morellato, 2004; Obeso, 2002; Octavio‐Aguilar, Iglesias‐Andreu, et al, 2017; Segalla, Pinheiro, & Morellato, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yearly variation in fruit set was larger in night‐open flowers than in day‐open flowers, suggesting that the pollinator activity was more unstable during nighttime in early spring, due to cool temperature. Several studies have reported that settling moths were inefficient or less important as pollinators in early‐blooming plants (Alonso, 2004; Jürgens et al, 2014; Funamoto and Sugiura, 2020). However, in the present study, both diurnal and nocturnal pollinators were effective in D. jezoensis .…”
Section: Discussionmentioning
confidence: 99%
“…This is because a generalized pollination system increases the opportunity for pollen transfer via a wide range of insect groups (Rathcke, 2003;Darling and Barrett, 2011). These reproductive characteristics have been reported frequently in early-blooming and alpine plants, whose flowering season is characterized by low temperatures and unstable weather conditions (Schemske et al, 1978;Alonso, 2004;Rosati et al, 2019;Funamoto and Sugiura, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generalized pollination is typical of high mountain species where pollinator availability is unpredictable (Funamoto & Sugiura, 2020). Notwithstanding, these two Magnolia species that cohabit in remnant Andean cloud forests do not share their floral visitors, underscoring their highly specialized insect relationships.…”
Section: Floral Visitorsmentioning
confidence: 99%